Emotional and Ecological Literacy for a More Sustainable Society - Panieri, Giuliana; Poto, Margherita Paola; Murray, Emily Margaret (Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2024)
XVIII, 208 p. 13 illus., 12 illus. in color.